California editor - Storke, Thomas M. (Thomas More), 1876-1971. (Los Angeles : Westernlore Press, 1958)
Memoirs of journalist and political activist Thomas M. Storke.
Introducing "Mr. Santa Barbara" : a preface by Walker A. Tompkins -- A Santa Barbara boyhood -- Horse and buggy days -- Launching a career -- S. P. [Southern Pacific] rule in California -- Early in the century -- National politics -- The coming of F. D. R. [Franklin Delano Roosevelt] -- The New Deal era -- My Washington adventure -- Middle of the century.
Also issued online.
Mode of access: Internet.
Keywords: Journalists; Journalists -- Biography; California -- Santa Barbara; Santa Barbara (Calif.) -- History; History; Biographies